Peningkatan Hubungan Sosial Siswa Terisolir Melalui Layanan Konseling Individu: Studi Kasus pada Siswa Sekolah Menengah - Riskika, Melani; Doa Cut Choly Berlian S; Baiq Mahyatun; Laela Nurul Fitri; Tina Hasuki; D. Cantika Rismadi; M. abdul Latif; Nurazella (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Healthy social relationships are one of the main pillars of students’ psychosocial and academic development at school. In reality, however, a number of students experience conditions of alienation or social isolation, marked by minimal interaction with peers, low involvement in group activities, and genuine difficulty in building meaningful interpersonal relationships. This study aims to describe in depth the process and outcomes of improving the social relationships of socially isolated students through individual counseling services. The study used a qualitative approach with an embedded case study design. The research subjects consisted of three secondary school students identified as socially isolated based on sociometric results, systematic observation, and recommendations from guidance and counseling teachers. Data were collected through participatory observation, semi-structured in-depth interviews, and counseling documentation. Data analysis referred to the model of Miles, Huberman, and Saldáña, comprising data condensation, data display, and iterative conclusion drawing. The validity of the data was ensured through source and technique triangulation. The results showed that individual counseling services conducted over six sessions significantly improved students’ social relationships through four main mechanisms: strengthening self-understanding, increasing self-confidence, developing interpersonal communication skills, and expanding involvement in group social activities. After receiving counseling, all subjects showed measurable behavioral changes, including an increase in the frequency of interaction with peers, courage in expressing opinions in class, and better social acceptance from the school environment. These findings confirm that individual counseling is an effective and relevant intervention in helping socially isolated students build more adaptive and functional social relationships.